2016
DOI: 10.11604/pamj.2016.23.259.8262
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health facility based maternal mortality in Central Region, Kenya: 2008-2012

Abstract: IntroductionWHO classifies Kenya as having a high maternal mortality. Regional data on maternal mortality trends is only available in selected areas. This study reviewed health facility maternal mortality trends, causes and distribution in Central Region of Kenya, 2008-2012.MethodsWe reviewed health records from July 2008 to June 2012. A maternal death was defined according to ICD-10 criterion. The variables reviewed included socio-demographic, obstetric characteristics, reasons for admission, causes of death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Obstetric haemorrhage contributed to 38% of all maternal deaths in the study period. Similar findings were recorded in a retrospective analysis of causes of health facility maternal deaths in Ogun state, Nigeria, and central regions of Kenya where haemorrhage was the leading cause accounting for 40% and 43.3%, respectively [ 6 , 11 ]. A study conducted at Shinyanga Regional Referral Hospital, Tanzania, also correlates to the above findings that haemorrhage was the leading cause of maternal deaths by 50% [ 12 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Obstetric haemorrhage contributed to 38% of all maternal deaths in the study period. Similar findings were recorded in a retrospective analysis of causes of health facility maternal deaths in Ogun state, Nigeria, and central regions of Kenya where haemorrhage was the leading cause accounting for 40% and 43.3%, respectively [ 6 , 11 ]. A study conducted at Shinyanga Regional Referral Hospital, Tanzania, also correlates to the above findings that haemorrhage was the leading cause of maternal deaths by 50% [ 12 ].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in their study, Luis Alvarez et al found that 34% of maternal deaths in Africa were due to haemorrhage [ 5 ]. In East Africa, a study conducted in the central region of Kenya showed that haemorrhage contributed to 40% of all causes of maternal deaths and the majority of these women died within 24 hours after admission [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of included articles by country was as follows:, Algeria [60], Benin [78], Burkina Faso [122,143], Cameroon [99,133], Democratic Republic of Congo [55,82], Egypt [105], Eritrea [102], Ethiopia [57,62,71,72,74,86,130,131], Ghana [49,52,53,58,69,141], Guinea-Bissau [76], Kenya [63,91,110,123,142,145], Madagascar [79], Malawi [80,83,100,126,140], Morocco [44], Mozambique [59], Nigeria [42,43,45,47,48,54,56,65,67,89,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Maternal mortality has decreased in Africa, especially in southern and high-income countries. The most important long-term factors are health policies and the accessibility of health services, which are influenced by the quality of care and road building construction that facilitates transportation to health facilities [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In future research, maternal mortality may be adjusted for potential risk factors, including income and education level, comorbidities, medical assistance, and environmental sanitation, to estimate maternal mortality trends [42][43][44][45] accurately.…”
Section: Discussionmentioning
confidence: 99%